Simulation and flesh: total cinema, virtual reality and 1930s science fiction. Issue 10 (3rd October 2021) - Ross, Miriam
ABSTRACT: At the turn of the twentieth century, ideas and technologies coalesced around the realisation of what Kim Timby calls the integral-image utopia: the complete simulation of the natural world. Later described as total cinema in the 1940s by André Bazin and René Barjavel, attention was placed on materially representing the sensible world through moving-image photography, sound, colour and depth. Yet only brief consideration was given to the flesh of the viewer, their embodied engagement with and subjective approach to this perceptual realism. It was the written word, arguably the most immaterial and least sensibly manifest media, that made the case for the role of the body. At the same time that experiments towards the integral-image utopia – particularly sound, colour and stereoscopic depth – became as known for their failures and intermittent uptake as their success, 1930s science fiction literature was able to develop the integral-image utopia through descriptions of proto virtual reality (VR) systems that centred the human body. Rather than a linear flow wherein literature adapted the ideas of technological experimentation, or technological realisation adapted and responded to ideas proposed in literature, cross-fertilising cyclical models of exchange between literature and audiovisual technologies took place.